ANALYSIS OF SATISFACTION VISITORS ON INCREASED PEOPLE`S INCOME TOURIST ATTRACTIONS IN CURUG NANGKA NATURAL TOURISM OBJECT HALIMUN SALAK MOUNTAIN NATIONAL PARK - Mamat Surahmat; Rosadi Rosadi; Rita Retnowati (Universitas Pakuan, 2021)
This study aims to determine the relationship between the quality of infrastructure and visitor satisfaction, knowing the relationship between service personnel and visitor satisfaction, knowing the relationship between the quality of infrastructure and service officers together with visitor satisfaction and knowing the relationship between visitor satisfaction and increased community economic income. in the natural attractions of Curug Nangka, Mount Halimun Salak National Park. The approach used in this research is a mixed method explanatory sequential design, which is a method of data collection that begins with quantitative data collection and then continues with qualitative data collection to help analyze. This research will begin with data collection that begins with quantitative data collection, which examines three variables. Research variables that will be used in this study consist of independent variables (independent variables), namely the X1 variable quality of infrastructure, X2 service of officers and the dependent variable (dependent variable), namely the variable Y visitor satisfaction. The quantitative data will be deepened by collecting qualitative data, namely to obtain information about the effect of visitor satisfaction with an increase in people's economic income in the natural tourism object of Curug Nangka, Mount Halimun Salak National Park. The data obtained by distributing questionnaires using a Likert scale. The population in quantitative research is the total number of visitors in 2020, namely 28,974 people / person and a sample of 100 people was drawn while the population and sample for qualitative research were 47 natural tourism actors. The data analysis model in this study used quantitative and qualitative analysis. The quantitative analysis used single and multiple regression analysis and correlation while the qualitative analysis used Miles and Hubermann (1984). The results showed that there was a moderate relationship between the quality of infrastructure and visitor satisfaction, a strong relationship between officer service and visitor satisfaction, and a very strong relationship between the quality of infrastructure and service officers together with visitor satisfaction and knowing a positive relationship. between visitor satisfaction and the increase in people's economic income in the natural tourism object of Curug Nangka, Mount Halimun Salak National Park.